Online Buying Behaviour of Netizens: A Study with Reference to Coimbatore, Tamil Nadu - Shalini, S.; Kamalaveni, D. (Indian Journal of Marketing, 2013)
The latest generation of commerce is one that can be done over the Internet. The Internet provides a virtual platform where sellers and buyers can come in contact for sale and purchase of goods and services. They can be thousands of miles apart, may belong to different parts of the world, and might speak different languages. E-Commerce has emerged as the boundary-less trade medium in the era of globalization. Since, the Internet has the ability to reach the customer's home, the distribution channels have started to assume new meaning for the B2C E-commerce. The physical delivery got converted to electronic delivery; physical products are now electronic products displayed on a website. With options of paying online through debit and credit cards, the transaction is purely electronic. For the present study, the data was collected with the help of a structured questionnaire from 226 respondents. The study brought to fore that online shoppers are young, highly educated, active, intensive, and expert users of the Internet; they have a strong positive perception towards online shopping and generally spend a very low amount on online shopping. Significant differences in shopping behavior could be ascribed to gender, occupation, and the Internet expertise of the online shoppers. The detailed findings and implications are discussed in the paper.